Skeletal Muscle Volume Is an Independent Predictor of Survival after Sorafenib Treatment Failure for Hepatocellular Carcinoma - Saeki, Issei (Cancers (Basel), 2021)
SIMPLE SUMMARY: Skeletal muscle volume has been reported as a prognostic factor for patients with hepatocellular carcinoma receiving sorafenib. In this study, we show that skeletal muscle volume is not only a predictor of overall survival but also of post-progression survival, which represents survival time following confirmation of progressive disease. We may be able to prolong survival by upregulating skeletal muscle volume, especially in hepatocellular carcinoma patients with skeletal muscle depletion. ABSTRACT: Few studies exist on the relationship between post-progression survival (PPS) and skeletal muscle volume in hepatocellular carcinoma (HCC) patients receiving sorafenib. This study aimed to analyze the effects of muscle volume on clinical outcomes. We retrospectively enrolled 356 HCC patients. Various clinical parameters, including skeletal muscle index, were analyzed as predictors of overall survival (OS), progression-free survival (PFS), and PPS. Patients with high muscle volume showed longer survival or PPS than those with low muscle volume (median survival time: 12.8 vs. 9.5 months, p = 0.005; median PPS: 8.2 vs. 6.3 months, p = 0.015); however, no differences in PFS were found. Multivariate analysis indicated that muscle volume was an independent predictor of PPS and OS. Skeletal muscle volume was a PPS predictor in HCC patients receiving sorafenib. Therefore, survival can be prolonged by the upregulation of skeletal muscle volume, especially in HCC patients with skeletal muscle depletion.